2018
DOI: 10.1002/adfm.201804394
|View full text |Cite
|
Sign up to set email alerts
|

Space‐Confined Growth of CsPbBr3 Film Achieving Photodetectors with High Performance in All Figures of Merit

Abstract: All-inorganic halide perovskite is considered as outstanding candidate of organic-inorganic hybrid perovskite due to its superior stability. However, the low solubility of precursor and uncontrollable film growth result in poor film quality and impede the application of polycrystalline films greatly. In this work it is reported on a space-confined growth strategy to overcome the low solubility and fast crystal growth disadvantages via freezing the precursor solution within the gaps of ordered polystyrene spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 49 publications
0
108
0
Order By: Relevance
“…C, Calculated responsivity and D, detectivity at a bias of 5 V. E, Power‐dependent photocurrent of photodetectors based on CsPbBr 3 IO film (PbBr 2 :CsBr = 1.2) under a bias of 5 V. F, −3 dB bandwidth of the photodetector at 1 V bias voltage. Source : Reproduced with permission from Reference Copyright 2018, John Wiley and Sons…”
Section: Photoconductive Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…C, Calculated responsivity and D, detectivity at a bias of 5 V. E, Power‐dependent photocurrent of photodetectors based on CsPbBr 3 IO film (PbBr 2 :CsBr = 1.2) under a bias of 5 V. F, −3 dB bandwidth of the photodetector at 1 V bias voltage. Source : Reproduced with permission from Reference Copyright 2018, John Wiley and Sons…”
Section: Photoconductive Photodetectorsmentioning
confidence: 99%
“…65 The recent advancements and applications on film photodetectors and the tactics of achieving high-quality film in photodetectors based on space-confined growth are summarized: Zeng et al reported space-confined growth tactics to surmount above-mentioned obstacle and realized a faster response speed. 66 The specific process of this strategy is shown in Figure 14. An ordered polystyrene (PS) sphere template was firstly fabricated.…”
Section: Photoconductive Photodetectorsmentioning
confidence: 99%
“…[1][2][3] The RRAM device, with sandwich structure of top metal (TE)/ switching layer/bottom metal (BE), can be switched between a low resistance state (LRS) and high resistance state (HRS) under the stimulation of different voltage amplitudes or polarities. [8] In recent years, halide perovskites, with formula of ABX 3 (A = CH 3 NH 3+ , CH(NH 2 ) 2+ , Cs + ; B = Pb 2+ , Sn 2+ ; X = Cl − , Br − , I − ), have attracted intensive attention due to their huge potential applications in industrial applications, such as solar cells, [9] photodetectors, [10] light emitting diodes, [11] lasers, [12] and RS memory devices. However, the perovskite oxide-based RRAM devices are limited by several disadvantages, such as high processing temperature and rigid ceramic property of the switching layer.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Compared to their 3D counterparts, these layered materials offer confined photocarriers, high-rate excitonic recombination, and enhanced environmental stability, which introduce core opportunities for realizing efficient and stable light-emitting diodes (LEDs), lasers, photodetectors, and solar cells. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] by chemical vapor deposition on epitaxial substrate. [32][33][34][35] For example, Jin and his colleagues developed epitaxial growth of single-crystalline perovskite structures on mica and SrTiO 3 substrates.…”
Section: Doi: 101002/adma201905298mentioning
confidence: 99%